Design and experimental study of a solar CPV system using CLFR concentrator. (August 2020) - Wang, Gang; Shen, Fan; Wang, Fasi; Chen, Zeshao
Highlights: A solar CPV system with CLFR concentrator is described. An experimental set-up of the CPV system is built for experimental study. Evaluation results reveal a high solar concentrating uniformity of the CPV system. Abstract: A solar concentration photovoltaic (CPV) system with compact linear Fresnel reflector (CLFR) concentrator is described in this paper. The design approach of the CPV system is introduced. Four different CLFRs are designed and compared, including one complete type and three hybrid type CLFRs. In order to evaluate the optical performance of the CPV system, solar concentration processes of the four CLFRs are simulated by using the MCRT method. The results indicate that the complete type CLFR (CLFR-c) has the highest concentrated solar radiation uniformity. An experimental set-up is built to carry out the evaluation of actual optical performance of the CLFR-c and a good agreement between the simulation and measurement results is demonstrated. The optical parameter analysis results of the CPV system reveal that the optimal solar panel height exists, which can result in the maximum ground utilization and concentration ratios. The influence of sun-tracking accuracy on the optical efficiency of the CPV system is analyzed. The results indicate that the normalized optical efficiency of the CLFR-c concentrator is 0.89 when the tracking error is 0.2°. The preliminary PV performance test results reveal a photoelectric conversion efficiency of 15.9% for the PV cell module installed on the solar CPV system.